(untitled) (Pulse, 2014)
Management of a complicated obstetric patient with profuse bleeding following caesarean section (under GA) required massive blood transfusion was managed properly with multidisciplinary approach in ICU. The involvement of obstetrician, anesthesiologist, intensivist, general surgeon, hematologist & gastroenterologist as a team in a single setup is essential for the management of such patients and the best outcome. The patient received total 117 units of blood products among which 20 units whole blood, 17 units packed red blood cell, 40 units of fresh frozen plasma and 40 units of platelet concentrate. Despite this massive blood transfusion, the patient recovered fully with minimal complications as we follow the near standard blood transfusion protocol. DOI: http://dx.doi.org/10.3329/pulse.v5i1.20189 Pulse Vol.5 January 2011 p.39-43